The roles of heat shock proteins 70 in enhancing the productive performances of livestock animals - Lerdweeraphon, Wichaporn (Veterinary Integrative Sciences, 2017)
Heat shock proteins 70 (HSP70s) are chaperone proteins that assist a wide range of folding processes, including protein aggregation, newly synthesized proteins, signal transduction, and control of the activity of regulatory proteins. Heat shock proteins are present in all the different subcellular compartments of all cell types of prokaryotes and eukaryotes. The elevated of cellular HSP70s synthesis result from exposing to heat stress. Among the HSPs, HSP70s have a significant role in cell thermotolerance and its expression acts as a potential indicator of animal adaptation to hot climate. It can be said that HSP70s may act as a biomarker of heat tolerance in large animals. In addition, HSP70s also have important roles in both male and female reproductive systems, including enhanced sperm fertilizing ability, survival of spermatozoa, embryo development, mainly responsible for mammary cell protection from heat stress, and stimulate immune system responses. Furthermore, HSP70s can be beneficial in the prevention and treatment of various human neurodegenerative diseases and cancer. Therefore, this review proposes recent evidences and hypotheses suggesting that HSP70s may be important roles in enhancing productive performances of livestock animals in the future.